Lance-Adams Syndrome: A Rare Neurological Condition Following Suicidal Hanging: A Case Report (Journal of Psychiatrists' Association of Nepal, 2026)
Background: Lance-Adams syndrome, also known as chronic hypoxic myoclonus, is a rare neurological condition following hypoxic brain injury.Case Presentation: A 21-year-old female patient presented to the Emergency Room with a Glasgow Coma Scale (GCS) of 6/15 and was intubated immediately. On the 4th day after regaining consciousness, she started to develop action-induced myoclonic jerks. Necessary examinations and investigations were done, after which the diagnosis of Lance-Adams syndrome was made. She was started on sodium valproate, and her symptoms improved on the 7th day of initiation of treatment.Conclusion: In survivors of hanging with hypoxic brain injury, the development of sudden myoclonus after regaining consciousness for a few days should raise suspicion of Lance-Adams syndrome. Early recognition and treatment with antimyoclonic agents should be initiated.